Evaluation of melatonin levels in saliva in periodontal health and disease: A clinico-biochemical study - Nilkanth Mhaske; Pramod Marawar; Anand Sheker; Nilesh Mote (Wolters Kluwer Medknow Publications, 2010)
Background: Melatonin, a secretory product of the vertebrate pineal gland, activates several elements of the immune system that reduce tissue destruction during the inflammatory response, either directly by scavenging free radical, reactive oxygen species and reactive nitrogen species or indirectly by modulating the action of agents such as cytokines and adhesion molecules, which contribute to the advance of cell damage. Aim: The aim of this study was to evaluate melatonin levels in saliva in periodontal health and disease. Materials and Methods: This study was conducted on a total of 20 patients with healthy periodontium and 20 patients each with mild, moderate and severe periodontitis who were patients in the Department of Periodontics, Rural Dental College and Hospital, Loni. The salivary levels of melatonin were assayed using ELISA, a competitive immunoassay using a capture antibody technique. Results: We observed that the periodontitis sufferers had a significantly lower melatonin level than the healthy subjects. Conclusion: Consequently, the reduction in the saliva production with higher age and the decreased melatonin production in older adults reflected in low salivary melatonin levels predispose these individuals to an increased risk of developing oral and periodontal disease.